Environmental Knowledge and Practices Among Students of Valley University of Science and Technology, Bushenyi, Uganda - Janan, Mubehamwe; Teddy, Kanyesigye Stella; Jackson, Nzarirwehi (Innovare Journal of Education, 2025)
Continuous environmental degradation has not only led to increased global warming but has also contributed to mortality rates as well as hindering economic progress. Unfortunately, there was a lack of literature on how educational institutions, especially those in Uganda and especially Valley University of Science and Technology, respond to issues of the environment interns of curricular and other general environmental education practices. Hence, this study investigated the knowledge and practices of environmental education among students, specifically those at Valley University of Science and Technology, Bushenyi, Southwestern Uganda. The study was quantitative and employed descriptive methods. A questionnaire on environmental education measured on a five Likert scale (1 = strongly disagree, 2 = disagree, 3 = not sure, 4 = agree, and 5 = strongly agree) was designed and administered online through WhatsApp and feedback was received from 190 respondents. The responses indicated that all students knew what factors lead to environmental degradation (mean of men = 4.21, mean of women = 4.12). It was also found that both students (mean of men = 2.77, mean of women = 2.82) and Valley University of Science and Technology as an institution (mean of men = 4.29, mean of women = 4.24) were environmentally responsive through their curriculum design, use of proper waste management methods, conduction of sensitization programs, and participating in tree planting programs. The level of knowledge and practices towards environmental sustainability among the respondents were found to be independent of students’ gender (p > .05). It was thus recommended that related programs be designed to sensitize all people as they exist in their different communities by putting up posters, conducting talks and performing skits on environmental education. Since the results proved that all the educated are literate about environmental education, legislators and environmentalists can base on them to put in place strict laws and policies against environmental degradation.